Potential Phosphorus Uptake Mechanisms in the Deep Sedimentary Biosphere - Delphine Defforey; Benjamin J. Tully; Jason B. Sylvan; Barbara J. Cade-Menun; Brandi Kiel Reese; Brandi Kiel Reese; Laura Zinke; Adina Paytan; Adina Paytan (Frontiers in Marine Science, 2022)
Our understanding of phosphorus (P) dynamics in the deep subseafloor environment remains limited. Here we investigate potential microbial P uptake mechanisms in oligotrophic marine sediments beneath the North Atlantic Gyre and their effects on the relative distribution of organic P compounds as a function of burial depth and changing redox conditions. We use metagenomic analyses to determine the presence of microbial functional genes pertaining to P uptake and metabolism, and solution 31P nuclear magnetic resonance spectroscopy (31P NMR) to characterize and quantify P substrates. Phosphorus compounds or compound classes identified with 31P NMR include inorganic P compounds (orthophosphate, pyrophosphate, polyphosphate), phosphonates, orthophosphate monoesters (including inositol hexakisphosphate stereoisomers) and orthophosphate diesters (including DNA and phospholipid degradation products). Some of the genes identified include genes related to phosphate transport, phosphonate and polyphosphate metabolism, as well as phosphite uptake. Our findings suggest that the deep sedimentary biosphere may have adapted to take advantage of a wide array of P substrates and could play a role in the gradual breakdown of inositol and sugar phosphates, as well as reduced P compounds and polyphosphates.